ANALISIS KOMPETENSI RESERVASI TICKET INTERNATIONAl ONLINE LULUSAN MAHASISWA PROGRAM STUDI USAHA PERJALANAN WISATA POLITEKNIK NEGERI BALI - Nyoman Mastiani Nadra; I Made Budiasa (Soshum: Jurnal Sosial dan Humaniora, 2014)
Education on Diploma III Travel & Tourism Study Program is aimed at generating power business associate professionals in the travel and tourism field. With the enactment of the President of the Republic of Indonesia Regulation No. 8 of 2012 on the Indonesia Qualifications Framework (KKNI) qualifications level of Indonesian human resources, the Education Studies Program Diploma of Business Travel at the level of 5 is in a position as a supervisor, it is necessary to support the level of competence 5 to support the necessary competence to analyze the competence of graduates by conducting research using the alumni of the last 2 years working in the field of ticketing as a sample. With the snowball method obtained 11 alumni and 3 supervisors ticketing to be interviewed in depth. Results achieved that competency is a skill that any 'key to operate the computer and use the internet and be able to operate online ticket reservation system using a program like Abacus reservation. Other skills should also be held as to understand the ticketing provisions in general, understand the common terms used in the operational flight by IATA, the basis for calculating the price of tickets, look for special fare and the condition (rule) of each special prices as well as to understand the geography of international flight. In addition to the core competencies to become competent resources necessary attributes required soft skills such as initiative, ethics / integrity of critical thinking, willingness to learn, commitment, motivation, enthusiastic, reliable, and creative verbal communication.